(untitled) (Revista Investigación & praxis en CS Sociales, 2025)
The rapid incursion of Artificial Intelligence (AI) into various social sectors raised significant questions for the educational field, which motivated the present research. This qualitative bibliographic study aimed to analyze the impact AI had on secondary and higher education within the Latin American context. To this end, the objectives behind AI implementation in these spheres, the basic procedures through which it was applied in teaching-learning processes and educational management, as well as the most relevant results reported in specialized literature, were examined. Similarly, the main conclusions and challenges that emerged from these experiences were identified. The methodology involved a systematic and exhaustive review of over 70 academic sources and specialized documents, preferably published in recent years, which addressed the applications, benefits, limitations, and ethical considerations of AI at the mentioned educational levels in the region. As a result, key emerging trends were identified, persistent knowledge gaps were highlighted, and future research lines were proposed to deepen the understanding of this constantly evolving phenomenon.